Techno-economic assessment and wind energy potential of Nagad in Djibouti - Idriss, Abdoulkader Ibrahim; Ahmed, Ramadan Ali; Atteyeh, Hamda Abdi; Omar, Abdou Idris; Akinci, Tahir Cetin (International Journal of Applied Power Engineering (IJAPE), 2024)
The use of small scaled horizontal and vertical axis wind turbines in urban installation is increasing over the world. However, in Djibouti, the latter is still in the development phase. The paper presents a techno-economical analysis and wind energy potential for the period of five years (2015-2019) in Nagad based on actual measured wind speed data collected every 10 min at 10 m height. The energy pattern factor method has been used to estimate the Weibull parameters. With this method, the mathematical complexity is reduced with a minimization of the error at any heights and locations when calculating the wind power density. At 50 m height, the shape parameter showed a small variation for different periods. The scale parameter values of 7.78 m/s and 4.8 m/s were obtained in the hot and cold seasons, respectively. The results showed that the Nagad site is suitable for wind power development. According to the economic viability, RX30, Vestas V20, Enercon, Nordex N27, and Vestas V44 wind turbines are recommended for the Nagad site due to their low energy price ranging from 0.05$/kWh to 0.31$/kWh. This is 2-6 times cheaper than the average local tariff of electricity in Djibouti.